(untitled) (Bulletin KNOB, 1997)
The dendrochronological datings now presented refer to houses with oakwood constructions, varying in age from the early 14th century to the middle of the 18th century. Because of the doctoral research of Esther Jansma (RING Amersfoort) and the application of Scandinavian Standard curves it was possible to date a number of buildings after all in 1995. From these datings it appears that the oakwood used for various buildings in the town of Groningen must have come from Scandinavia or the Baltic Provinces. In 1571, for instance, Scandinavian pinewood and oakwood were simultaneously used in Turftorenstraat 13 in Groningen. At the time of the Twelve-Year Truce (1609-’21) this Scandinavian pinewood was being applied in buildings throughout The Netherlands, with the exception perhaps of some eastern provinces, where oakwood roof constructions were still customary until into the 18th century (monastery St Gerlach at Houthem around 1710 and castle Genhoes in Oud-Valkenburg in 1750). Generally, the datings of houses presented here are connected with research by building historians working privately or in public service.